2017
DOI: 10.3310/hta21670
|View full text |Cite
|
Sign up to set email alerts
|

CollAborative care for Screen-Positive EldeRs with major depression (CASPER plus): a multicentred randomised controlled trial of clinical effectiveness and cost-effectiveness

Abstract: This journal is a member of and subscribes to the principles of the Committee on Publication Ethics (COPE) (www.publicationethics.org/).Editorial contact: journals.library@nihr.ac.ukThe full HTA archive is freely available to view online at www.journalslibrary.nihr.ac.uk/hta. Print-on-demand copies can be purchased from the report pages of the NIHR Journals Library website: www.journalslibrary.nihr.ac.uk Criteria for inclusion in the Health Technology Assessment journalReports are published in Health Technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…The editorial6 published by The BMJ in 2004 proposed Collaborative Care to help older people with depression, especially those with chronic physical and social problems, and there have been recent positive findings from a large UK trial 12…”
Section: A Different Approachmentioning
confidence: 99%
“…The editorial6 published by The BMJ in 2004 proposed Collaborative Care to help older people with depression, especially those with chronic physical and social problems, and there have been recent positive findings from a large UK trial 12…”
Section: A Different Approachmentioning
confidence: 99%
“…A suggested recruitment strategy for future studies would be to send invitations to people aged > 65 years with two or more long-term physical conditions rather than to all registered patients aged > 65 years, as in the CASPER plus trial. [42][43][44] An alternative approach in future studies would be to recruit people already on antidepressants, as nearly half of participants in the NOTEPAD study were taking medication. Aiming to recruit people who live alone is difficult as 'living alone' is unlikely to be Read coded on GP computer systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the CASPER plus (CollAborative care for Screen-Positive EldeRs with major depression) trial, [42][43][44] the BA intervention was acceptable for many of the older adults with depression and could readily be delivered over the telephone, following a face-to-face meeting. This approach may be able to reduce the stigma of the label of mental illness and resolve misconceptions around antidepressant medication prescribed by GPs.…”
Section: Figurementioning
confidence: 99%
“…10). The substantial heterogeneity of 81% was due to higher costs of intervention reported by Bosanquet et al [46].…”
Section: Economic Outcomesmentioning
confidence: 95%
“…Meta-analysis of thirty-one studies [13, 14, 18, 19, 36, 38, 40, 42, 43, 46, 50, 51, 53, 55, 57, 63, 67, 68, 70, 76, 78, 83, 84, 86-88, 91, 93, 100, 102, 109] of patients with minor or major depression episodes after PCMH-based care reported signi cant improvement in depression scores compared to patients with standard primary care. With the exceptions of three studies [46,91,102], twentytwo studies reporting changes in mean differences (continuous data) of depression scores showed signi cant reduction with a pooled SMD of -0.24 (95% CI -0.35, -0.14; p-value < 0.001) (Fig. 3).…”
Section: Depression Outcomesmentioning
confidence: 97%